Influence of the physical terrestrial Arctic in the eco‐climate system. Issue 8 (1st December 2013) - Saito, Kazuyuki; Zhang, Tingjun; Yang, Daqing; Marchenko, Sergei; Barry, Roger G.; Romanovsky, Vladimir; Hinzman, Larry
Abstract : This synthesis paper provides a summary of the major components of the physical terrestrial Arctic and the influences of their changes upon the larger eco‐climate system. Foci here are snow cover, permafrost, and land hydrology. During the last century, snow cover duration has shortened in a large portion of the circum‐Arctic, mainly because of its early northward retreat in spring due to warming. Winter precipitation has generally increased, resulting in an increase in maximum snow depth over large areas. This is consistent with the increase in river discharge over large Russian watersheds. Soil temperature has also increased, and the active layer has deepened in most of the permafrost regions, whereas thinning of the seasonally frozen layer has been observed in areas not underlain by permafrost. These active components are mutually interrelated, conditioned by ambient micro‐ to landscape‐level topography and local surface and subsurface conditions, and they are closely related with vegetation and ecology, as evidenced by evolution in the late Quaternary. Further, we provide examples and arguments for discussions on the pathways through which changes in the Arctic terrestrial system can affect or propagate to remote areas beyond the Arctic, reaching to the extratropics in the larger climate system. These considerations include dynamical and thermodynamical responses and feedbacks, modification of hemisphere‐scale atmospheric circulation associated with troposphere–stratosphere couplings, and moisture intrusion at a continental scale.